# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+\frac {a y}{x^{{3}/{2}}} = 0
\] |
✓ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }-\left (x^{2}+4 x \right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) y^{\prime \prime }+\left (-x^{2}+1\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}4 x \left (1-x \right ) y^{\prime \prime }-4 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime }+y = x^{{3}/{2}}
\] |
✓ |
✗ |
|
\[
{}2 x^{2} y^{\prime \prime }-\left (3 x +2\right ) y^{\prime }+\frac {\left (2 x -1\right ) y}{x} = \sqrt {x}
\] |
✓ |
✗ |
|
\[
{}\left (-x^{2}+x \right ) y^{\prime \prime }+3 y^{\prime }+2 y = 3 x^{2}
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }+\left (\frac {3}{2}-2 x \right ) y^{\prime }-\frac {y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1-x \right ) y^{\prime \prime }+\left (1-11 x \right ) y^{\prime }-10 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }+\frac {\left (1-2 x \right ) y^{\prime }}{3}+\frac {20 y}{9} = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1-x \right ) y^{\prime \prime }+y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+\frac {3 \left (-x^{2}+2\right ) y}{\left (-x^{2}+1\right )^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x y+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x^{2} y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -4 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime \prime }-x^{2} y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 y^{\prime }-x y = 0
\] |
✓ |
✗ |
|
\[
{}\left (x^{2}-2\right ) y^{\prime \prime }+2 y^{\prime }+y \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+x \right ) y^{\prime \prime }+3 y^{\prime }-6 x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}-t -2\right ) x^{\prime \prime }+\left (t +1\right ) x^{\prime }-\left (t -2\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+\left (1-x \right ) y^{\prime }+\left (x^{2}-2 x +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} y^{\prime \prime }-\left (x^{2}-1\right ) y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }-y \ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}z^{\prime }-x^{2} z = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (x -1\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}w^{\prime \prime }-x^{2} w^{\prime }+w = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x -3\right ) y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime \prime }-3 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+x +1\right ) y^{\prime \prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-5 x +6\right ) y^{\prime \prime }-3 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\tan \left (x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime \prime }-x y^{\prime }+2 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 \left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-2 x \right ) y^{\prime \prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+\sin \left (t \right ) x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \,{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-{\mathrm e}^{x} y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t y^{\prime }+{\mathrm e}^{t} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-{\mathrm e}^{2 x} y^{\prime }+y \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}w^{\prime }+w x = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}z^{\prime \prime }+x z^{\prime }+z = x^{2}+2 x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x y^{\prime }+3 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }+2 y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-y^{\prime }+y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y \sin \left (x \right ) = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+n \left (n +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime \prime }+\frac {y^{\prime }}{x}+x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime }+y = 0
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime } = x^{2}-y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1-x +2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x^{2}+3 y
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = x^{2}-2 x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+p \left (p +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y = x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}2 \left (x^{3}+x^{2}\right ) y^{\prime \prime }-\left (-3 x^{2}+x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+2 \left (1-x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (-x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (1+x \right ) y^{\prime \prime }+x \left (1+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+y^{\prime }-y = 1+x
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y^{\prime \prime }+x^{2} y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime }+\left (x^{2}+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}z^{\prime \prime }+t z^{\prime }+\left (t^{2}-\frac {1}{9}\right ) z = 0
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+2\right ) y^{\prime \prime }-\left (x^{2}+4 x +2\right ) \left (\left (1-x \right ) y^{\prime }+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (1+x \right ) y^{\prime \prime }-\left (2 x +1\right ) \left (x y^{\prime }-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} \left (1+x \right ) y^{\prime \prime \prime }-\left (2+4 x \right ) x^{2} y^{\prime \prime }+\left (4+10 x \right ) x y^{\prime }-\left (4+12 x \right ) y = 0
\] |
✓ |
✓ |
|